2003
DOI: 10.14430/arctic604
|View full text |Cite
|
Sign up to set email alerts
|

Molt Migration in Relation to Breeding Success in Greater Snow Geese

Abstract: ABSTRACT. We describe summer migratory movements by female greater snow geese (Chen caerulescens atlantica) breeding on Bylot Island, Nunavut. We followed 121 radio-collared females between 1997 and 2001 to determine the frequency and timing of their departure from the colony in relation to breeding status, nesting success, and molting chronology. We found that 90% (n = 51) of non-breeders (no nest found) and 97% (n = 29) of failed nesters (nest destroyed or abandoned before hatch) departed the island before m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 16 publications
3
42
0
Order By: Relevance
“…Previous research on moulting migration showed that the breeding performance of geese species had a strong influence on moulting migration patterns: the majority of successful breeders moulted on or near the breeding grounds, whereas most non-breeders and failed breeders left the breeding grounds to moult elsewhere (Bollinger and Derksen 1996;Reed et al 2003;Luukkonen et al 2008). In our study, it appeared that successful breeders moulted on the breeding grounds.…”
Section: Discussionsupporting
confidence: 51%
“…Previous research on moulting migration showed that the breeding performance of geese species had a strong influence on moulting migration patterns: the majority of successful breeders moulted on or near the breeding grounds, whereas most non-breeders and failed breeders left the breeding grounds to moult elsewhere (Bollinger and Derksen 1996;Reed et al 2003;Luukkonen et al 2008). In our study, it appeared that successful breeders moulted on the breeding grounds.…”
Section: Discussionsupporting
confidence: 51%
“…With the help of a helicopter, groups of moulting geese and their young were herded into corral traps by people on foot (see Menu et al 2001 for details). Most of the captured birds were successful nesters with their young of the year, as most nonbreeders and failed-nesters had left the island to moult elsewhere or had regained flight capacity at the time of banding (Reed et al 2003). All birds captured for the first time were fitted with a metal US Fish and Wildlife Service leg band.…”
Section: Field Methodsmentioning
confidence: 99%
“…This northward migration was thought to be a molt migration. When geese molt, they lose both flight and tail feathers and are rendered flightless (Reed et al 2003). Birds taking part in a molt migration are generally the nonbreeders or failed breeders.…”
Section: Discussionmentioning
confidence: 99%